2020
DOI: 10.17718/tojde.849870
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Experiences and Perceptions of Online Collaborative Learning in Higher Education of Korea and the Uae

Abstract: The purpose of this study was to compare the experiences and perceptions of UAE and Korean students in campus-based universities of online collaborative learning (OCL). 262 college students participated in online surveys. Their experiences in terms of frequency, assessment, barriers, support, and attitude for OCL in each country were examined. With Importance-Performance Analysis, the perceived importance of OCL activities was compared with actual frequency. Both countries' students experienced group projects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
4
9
1
Order By: Relevance
“…Moreover, the students felt that they enjoyed writing more than they did before due to the online collaborative environment as expressed in item 25 (M= 4.40) and the experience helped them work in a more relaxed atmosphere 20 (M= 4.37). This is in line with several studies (Farrah, 2015;Lee & Osman, 2021;Rezeki, 2017;Kalayci, 2014).…”
Section: Online Collaborative Behaviorssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, the students felt that they enjoyed writing more than they did before due to the online collaborative environment as expressed in item 25 (M= 4.40) and the experience helped them work in a more relaxed atmosphere 20 (M= 4.37). This is in line with several studies (Farrah, 2015;Lee & Osman, 2021;Rezeki, 2017;Kalayci, 2014).…”
Section: Online Collaborative Behaviorssupporting
confidence: 92%
“…Item 28 lent support for this perception as most of the students perceived online collaborative writing as an essential experience (m=4.49). This is in line with Farrah (2015), Azodi et al (2020), and Lee and Osman (2021) who reported joyful experiences of their participants regarding receiving constructive feedback and considering collaboration as an enjoyable experience.…”
Section: Online Collaborative Behaviorssupporting
confidence: 86%
See 3 more Smart Citations